2012
DOI: 10.5032/jae.2012.01162
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Abilities and Beliefs of Ohio Secondary Agricultural Education Mentor Teachers

Abstract: Nearly half of all new teachers leave teaching within the first five years of entering the profession. The exodus from the teaching profession has placed teacher recruitment and retention as an important challenge for public education in the United States. In order for the workforce of teachers to remain sustainable; the field of education recognizes the need for professional development programs, particularly novice teacher induction, to combat the teacher attrition challenge. A number of studies determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Additionally, successful student teaching opportunities were also linked to appropriately implemented and supported mentoring relationships (Jones, Kelsey, & Brown, 2014). Foor and Cano (2012) suggested that an analysis of mentor's abilities and beliefs was one of the critical antecedents for a successful mentoring relationship and positive mentee outcomes. However, a further investigation of mentoring relationship within agricultural education contexts have been recommended (Jones et al, 2014).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Additionally, successful student teaching opportunities were also linked to appropriately implemented and supported mentoring relationships (Jones, Kelsey, & Brown, 2014). Foor and Cano (2012) suggested that an analysis of mentor's abilities and beliefs was one of the critical antecedents for a successful mentoring relationship and positive mentee outcomes. However, a further investigation of mentoring relationship within agricultural education contexts have been recommended (Jones et al, 2014).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The relationship between the mentor and protégé is one of the largest factors of an effective professional relationship for both parties (Hudson & Hudson, 2017). Still, mentoring programs can serve to increase teacher retention (Foor & Cano, 2012). Solomonson et al (2018) included teacher preparation and development as a contributing factor to the retention or attrition of a SBAE teacher.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%